Paracoccidioides spp. ferrous and ferric iron assimilation pathways - Bailão, Elisa Flávia L. C.; Lima, Patrícia de Sousa; Silva-Bailão, Mirelle G.; Bailão, Alexandre M.; Fernandes, Gabriel da Rocha; Kosman, Daniel J.; Soares, Célia Maria de Almeida (Frontiers in Microbiology, 2015)
Iron is an essential micronutrient for almost all organisms, including fungi. Usually, fungi can uptake iron through receptor-mediated internalization of a siderophore or heme, and/or reductive iron assimilation (RIA). Traditionally, the RIA pathway consists of ferric reductases (Fres), ferroxidase (Fet3) and a high-affinity iron permease (Ftr1). Paracoccidioides spp. genomes do not present an Ftr1 homolog. However, this fungus expresses zinc regulated transporter homologs (Zrts), members of the ZIP family of membrane transporters that are able in some organisms to transport zinc and iron. A 2,3,5-triphenyltetrazolium chloride (TTC)-overlay assay indicates that both Pb01 and Pb18 express a ferric reductase activity; however, 59Fe uptake assays indicate that only in Pb18 is this activity coupled to a reductase-dependent iron uptake pathway. In addition, Zrts are up-regulated in iron deprivation, as indicated by RNAseq and qRT-PCR using Pb01 transcripts. RNAseq strategy also demonstrated that transcripts related to siderophore uptake and biosynthesis are up-regulated in iron-deprived condition. The data suggest that the fungus could use both a non-classical RIA, comprising ferric reductases and Fe/Zn permeases (Zrts), and siderophore uptake pathways under iron-limited conditions. The study of iron metabolism reveals novel surface molecules that could function as accessible targets for drugs to block iron uptake and, consequently, inhibit pathogen’s proliferation.